A Long Road to Brexit: How Britain came to leave the EU - Kim, Keechang (Journal of East Asia and international law, 2016)
In a referendum held in 2016, Britain voted to leave the EU. Britain’s membership of the EU has been a difficult one. Unlike the other leading Member States of the EU, Britain did not seem to have a firm conviction that “ever-closer union” of the peoples of Europe is essential to the peace and liberty of Europe. In the wake of increased immigration and the recent refugee crisis, the British people chose to leave the EU in order to have their sovereignty and independence re-affirmed. It remains to be seen what will be the economic consequences of this largely political decision.